Appendectomy as a Risk Factor for Bacteremic Biliary Tract Infection Caused by Antibiotic-Resistant Pathogens. (15th May 2017) - Kawanishi, Koki; Kinoshita, Jun; Abe, Hiroko; Kakimoto, Tetsuhiro; Yasuda, Yuko; Hara, Takeshi; Kato, Jun
Abstract : Background/Aims . Recent evidence has suggested that appendix plays a pivotal role in the development and preservation of intestinal immune system. The aim of this study is to examine whether prior appendectomy is associated with an increased risk for the development of antibiotic-resistant bacteria in bacteremia from biliary tract infection (BTI). Methods . Charts from 174 consecutive cases of bacteremia derived from BTI were retrospectively reviewed. Using multivariate analysis, independent risk factors for development of antibiotic-resistant bacteria were identified among the clinical parameters, including a history of appendectomy. Results . In total, 221 bacteria strains were identified from 174 BTI events. Of those, 42 antibiotic-resistant bacteria were identified in 34 patients. Multivariate analysis revealed that prior appendectomy (Odds ratio (OR), 3.02; 95% confidence interval (CI), 1.15–7.87; p = 0.0 26 ), antibiotic use within the preceding three months (OR, 3.06; 95% CI, 1.26–7.64; p = 0.0 13 ), and bilioenteric anastomosis or sphincterotomy (OR, 3.77; 95% CI, 1.51–9.66; p = 0.00 46 ) were independent risk factors for antibiotic-resistant bacteria. Conclusions . Prior appendectomy was an independent risk factor for the development of antibiotic-resistant bacteria in bacteremia from BTI.